STANDAR OPERASIONAL PROSEDUR (SOP) PEMBINAAN BAGI NARAPIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II A KEROBOKAN - Ganda Gunawan Sarjana, I Nyoman; Rai Setiabudhi, I Ketut; Yusa Darmadi, A. A. Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 05, November 2013)
Drugs are substances that are beneficial to certain diseases according to the rules, but if misused will be a bad impact on society. Hence the need for Guidance System and appropriate Standard Operating Procedures in a correctional institution to overcome many drug cases. Within this study, using empirical normative and Historical Approach and The Statute Approach in order to understand and reduce bias in the case of narcotics in the community.
Keywords: Drugs, Guidance Systems, Standard Operating Procedures